Oncology Guidelines Usage in a Low- and Middle-Income Country - Nofisat Ismaila; Omolola Salako; Jimoh Mutiu; Oladeji Adebayo (Journal of Global Oncology, 2018)
Purpose: There is a paucity of data about current usage of oncology guidelines in low- and middle-income countries (LMICs), specifically in terms of the availability and quality of those guidelines. Our objective was to determine usage of oncology guidelines and the barriers and facilitators to their usage among radiation oncologists in LMICs. Methods: An online cross-sectional survey was conducted among practicing radiation oncologists in Nigeria via e-mail and the social media database of the Association of Radiation and Clinical Oncologists of Nigeria. In addition, paper questionnaires were administered at regional clinical meetings. Results: The survey response rate was 53.4% in a sample of 101 radiation oncologists from the database. Sixty-nine percent of respondents were consultants and 30% were residents. Approximately 43% had < 5 years’ experience. All of the respondents were involved in administering chemotherapy during the treatment of patients with cancer, whereas approximately half were involved in diagnosing cancer. Ninety-three percent reported using guidelines in treating patients, the top two guidelines being those from the National Comprehensive Cancer Network (90%) and the American Society of Clinical Oncology (50%). The two major barriers to guideline usage were that facilities were inadequate for proper guideline implementation and that the information in guidelines were too complex to understand. Potential facilitators included providing adequate facilities, developing local guidelines, and increasing awareness of guideline usage. Conclusion: Our study shows that clinicians involved in the treatment of patients with cancer in LMICs are aware of cancer treatment guidelines. However, implementation of these guidelines hinders their usage because the facilities are inadequate, guidelines are not applicable to the local setting, and the information in the guidelines is too complex.